2019
DOI: 10.1021/acs.est.8b06904
|View full text |Cite
|
Sign up to set email alerts
|

Cotransport and Deposition of Iron Oxides with Different-Sized Plastic Particles in Saturated Quartz Sand

Abstract: The present study was designed to investigate the cotransport and deposition of different-sized plastic particle from nano-(0.02 μm) to micrometer-scale (0.2 and 2 μm) with goethite and hematite (two types of representative iron oxides abundant in natural environment) in porous media at both low (5 mM) and high ionic strength (25 mM) in NaCl solutions. We found that through different mechanisms (i.e., modification of surface properties of iron oxides, steric repulsion, or alteration in deposition sites on quar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(51 citation statements)
references
References 57 publications
5
45
1
Order By: Relevance
“…Iron oxides are common forms of geochemical heterogeneity ubiquitously present in natural soil and sediment aquifers with concentrations ranging from μg L −1 to mg L −1 [23,39]. Our results generated from this research demonstrated that the presence of iron oxide coatings significantly decreased the mobility of GO and Cu-loaded GO in water-saturated sand columns.…”
Section: Discussionmentioning
confidence: 62%
“…Iron oxides are common forms of geochemical heterogeneity ubiquitously present in natural soil and sediment aquifers with concentrations ranging from μg L −1 to mg L −1 [23,39]. Our results generated from this research demonstrated that the presence of iron oxide coatings significantly decreased the mobility of GO and Cu-loaded GO in water-saturated sand columns.…”
Section: Discussionmentioning
confidence: 62%
“…In the quartz sand (300-425 μm in size) column, the breakthrough rate of 0.2 and 2 μm MPs reduced from 73% to ~27% and from 82% to ~2% after addition of iron oxides, respectively. Li et al (2019a) The mobility of PS MPs/NPs in nature soil decreased with the increasing contents of Fe…”
Section: Soil Mineralsmentioning
confidence: 97%
“…As abundant metal minerals in the soil (Li et al, 2019a), iron oxide and clay minerals are positively charged and may in 21 days at 20 ± 2°C in greenhouse pot experiment. Rillig et al, (2017) The adsorption capacity of HDPE MPs (48-58 μm, 100-154 μm, 0.6-1.0 mm and 1.0-2.0 mm) in the farmland soil for Cd 2+ decreases with the increasing particle size (from 1,473.21 to 1,433.79 mg kg −1…”
Section: Soil Mineralsmentioning
confidence: 99%
“…When these particles are released to the environment, further surface modifications will occur as the particles interact with other constituents, such as inorganic ions, dissolved organic matter, or extracellular polymeric substances (Cho et al, 2014;Wu, Jiang, Lin, & Ouyang, 2019). Their fate and transport in porous media, such as soils or sediments, will then be affected by their modified surface properties (Li, He, et al, 2019;Tong, He, Rong, Li, & Kim, 2020).…”
Section: Primary Micro-and Nanoplasticsmentioning
confidence: 99%
“…For example, organic matter can adsorb onto the surfaces of polystyrene microspheres and collectors, contributing to the repulsive interaction energy, and thus can reduce the deposition of microspheres (Franchi & O'Melia, 2003). On the other hand, iron oxides can lead to decreased transport of plastic particles (2 μm) through modification in surface properties of plastic particles and creation of additional deposition sites on collector surfaces (Li, He, et al, 2019). The cotransport of plastic particles with other substances induces alterations in the abovementioned mechanisms by providing or blocking retention sites, as well as by increasing or decreasing particle mobility.…”
Section: Model Micro-and Nanoplasticsmentioning
confidence: 99%